EU countries from central and Eastern Europe, and the investment development path model: a new assessment - Trąpczyński, Piotr; Gorynia, Marian; Nowak, Jan; Wolniak, Radosław (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
In the context of the investment development path (IDP) model, a comparative analysis is conducted of the IDPs of eleven Central and Eastern European (CEE) countries, all members of the European Union. The main purpose of the paper is to determine the timing and explore the factors that have influenced the movement of these eleven CEE economies through their IDP stages. The authors try to identify the current positioning of the CEE countries on the IDP, using both a graph depicting the relationship between net outward investment position (NOIP) per capita and GDP per capita, as well as detailed data on inward and outward FDI stocks and NOIP’s absolute values presented in Tables. Thereafter, the authors focus on the CEE-11 countries’ outward FDI and apply the outward FDI performance index in their analysis of country IDP positioning. In the concluding section, the authors summarize their findings and reveal the need to add new theoretical considerations to the original IDP model
Argumenta Oeconomica, 2019, Nr 2 (43), s. 385-406
Keywords: Investment Development Path; foreign direct investment; Central and Easter Europe; economic development